Bridging the gap of vision restoration - Carleton, Maya; Oesch, Nicholas W. (Frontiers in Cellular Neuroscience, 2024)
Retinitis pigmentosa (RP) and Age-Related Macular Degeneration (AMD) are similar in that both result in photoreceptor degeneration leading to permanent progressive vision loss. This affords the possibility of implementing vision restoration techniques, where light signaling is restored to spared retinal circuitry to recreate vision. There are far more AMD patients1, yet more resources have been put towards researching and developing vision restoration strategies for RP despite it rarity, because of the tractability of RP disease models. The hope is that these therapies will extend to the AMD population, however, many questions remain about how the implementation of prosthetic or optogenetic vision restoration technologies will translate between RP and AMD patients. In this review, we discuss the difference and similarities of RP and AMD with a focus on aspects expected to impact vision restoration strategies, and we identify key gaps in knowledge needed to further improve vision restoration technologies for a broad patient population.